Fairness of financial penalties to improve control of Clostridium difficile. (20th November 2008) - Walker, A Sarah; Spiegelhalter, David; Crook, Derrick W; Wyllie, David; Morris, James; Peto, Tim E A
Abstract : Trusts in England have been given targets to reduce C difficile infection rates. But Sarah Walker and colleagues argue that the way they are calculated makes financial penalties almost impossible to avoid